Hierarchically Macro‐/Mesoporous Polymer Foam as an Enhanced and Recyclable Catalyst System for the Sustainable Synthesis of 5‐Hydroxymethylfurfural from Renewable Carbohydrates. Issue 1 (18th September 2015) - Zhang, Yunlei; Chen, Yao; Shen, Yating; Yan, Yongsheng; Pan, Jianming; Shi, Weidong; Yu, Longbao
Abstract: Renewable and abundant carbohydrates are being strongly focused upon as a green and sustainable alternative for the production of valuable chemicals and biofuels. In this study, we chemically integrated acid–base bifunctionalized mesoporous silica nanoparticles (MSNs‐SO3 H‐NH2 ) and a macroporous polymer foam poly(HIPE) (PH) matrix that is derived from water‐in‐oil (W/O) high internal phase emulsion (HIPE) templating. After the subsequent sulfonation process, a SPHs@MSNs‐SO3 H‐NH2 catalyst with a hierarchical porous structure and bifunctional sites was prepared and used for the highly efficient synthesis of top value‐added 5‐hydroxymethylfurfural (HMF) from renewable cellulose in an ionic liquid (i.e., 1‐ethyl‐3‐methylimidazolium chloride, [EMIM]Cl) based system. Evaluation of the catalytic activity revealed that the designed macropores were favorable for ready mass transfer, whereas the high surface area for active‐site anchoring provided by the mesoporous structure was beneficial in enhancing the catalyst performance. A theoretical study also suggested that acidic and basic active sites synergistically work for the transformation reaction. Under the optimized conditions, a remarkably high HMF yield (44.5 %) was obtained efficiently. Furthermore, the as‐prepared catalyst was recycled in four consecutive cycles with a total loss of only 4.9 % activity. Abstract : Sweet success : Hierarchically macro‐/mesoporous polymer foam has been successfully synthesized and used for the sustainable production of 5‐hydroxymethylfurfural (HMF; see figure) from renewable cellulose. The as‐prepared catalyst was also effective for the conversion of glucose and fructose to HMF in a DMSO/H2 O system.